2019
DOI: 10.1590/s1677-5538.ibju.2018.0799
|View full text |Cite
|
Sign up to set email alerts
|

3D Reconstruction and physical renal model to improve percutaneous punture during PNL

Abstract: _______________________________________________________________________________________ Introduction and Objectives: We aim to present the use of 3D digital and physical renal model (1-5) to guide the percutaneous access during percutaneous nephrolithotripsy (PNL). Materials and Methods: We present the clinical case of a 30 years old man with left renal stone (25x15 mm). A virtual 3D reconstruction of the anatomical model including the stone, the renal parenchyma, the urinary collecting system (UCS) and the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Thus, conventional 2-dimensional (2D) cross-sectional images are unable to identify the exact intrarenal vascular anatomy and to predict the real tumor blood supply from segmental branches. 11 Recently, some authors reported that 3-dimensional (3D) models elaborated from conventional 2D imaging 11,12 can be used as additional tools to improve the understanding of the size, location, and depth of a renal mass and its vascular anatomy before PN. 13 The highfidelity 3D reconstruction of renal vasculature allows the surgeon to be more confident with selective or super-selective clamping 14 and to change the preoperative plan based on 2D imaging toward a more selective clamping approach.…”
Section: Clinical Practice Pointsmentioning
confidence: 99%
“…Thus, conventional 2-dimensional (2D) cross-sectional images are unable to identify the exact intrarenal vascular anatomy and to predict the real tumor blood supply from segmental branches. 11 Recently, some authors reported that 3-dimensional (3D) models elaborated from conventional 2D imaging 11,12 can be used as additional tools to improve the understanding of the size, location, and depth of a renal mass and its vascular anatomy before PN. 13 The highfidelity 3D reconstruction of renal vasculature allows the surgeon to be more confident with selective or super-selective clamping 14 and to change the preoperative plan based on 2D imaging toward a more selective clamping approach.…”
Section: Clinical Practice Pointsmentioning
confidence: 99%
“…In the last two decades, new tools based on three-dimensional (3D) imaging and advanced digital technologies have become available to surgeons during pre-, intra-and postoperative phases of an intervention in the cranio-maxillofacial field [4][5][6][7][8], as well as in other surgical specialties, such as neurology, urology, vascular surgery, orthopedics [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 3D reconstruction has been used as an adjuvant in percutaneous nephrolithotripsy. Bianchi et al observed that it may be helpful to reduce operative time and improve the learning curve (15).…”
Section: Discussionmentioning
confidence: 99%